Leveled Texts for Classic Fiction : Fantasy and Science Fiction. - Paris, Stephanie (Leveled Texts., 2013)
Differentiate instruction with excerpts from 15 classic works of fantasy/science fiction written at four different reading levels. Each text focuses setting, character, plot, or language usage and can be used for close reading or small-group instruction.